Avaliação dos aspectos anatômicos e funcionais do canal anal em mulheres com parto vaginal e sintomas de incontinência fecal - Dealcanfreitas, Iris Daiana (2016)
Faecal incontinence (FI) affects up to 24% of the female population and has a significant impact on quality of life. Different risk categories for the FI have been described. Women with previous vaginal delivery make up the majority of affected individuals. Proper evaluation of this condition, including use of FI scores and functional and anatomical measurements plays a key role in patient management. The study proposes to evaluate anatomical and functional measures of the anal sphincter using three-dimensional ultrasonography (3D US) and anorectal manometry (ARM) in incontinent women with vaginal delivery, to correlate the findings with symptoms of FI and to evaluate the effect of vaginal delivery of anatomy and function of the anal canal. Women with symptoms of FI and vaginal delivery were evaluated with Wexner incontinence score, ARM and 3D US. A control group of asymptomatic nulliparous was included. Resting and contraction pressure, the radial angle of the defect and the length of the external anal sphincter (EAS), the internal anal sphincter (IAS) anterior and posterior, the subsequent EAE + puborectalis muscle (PR) and gap were measured and correlated with scores. Of the 62 women, 49 showed symptoms of FI and 13 were nulliparous asymptomatic. Twenty-five had EAE defects, 8 had combined defect EAS and IAS, 16 had intact sphincters and continence scores were similar. Individuals with sphincter defects had lesser EAS and IAS anterior compared to women without defects. Those with a vaginal birth had less anterior EAS intact compared to nulliparous women. It revealed a correlation between resting pressure and the measure of EAS earlier and IAS in patients with sphincter defects. FI symptoms did not correlate with anal pressure and changes in the anal sphincter. Women with vaginal delivery have less anterior EAS and gap bigger and there were correlations of these with lower resting pressure.